Extending the German labor market ontology with online data - Martić, Diana [Verfasser]; Fischer, Andreas [Verfasser]; Dörpinghaus, Jens [Verfasser] (My University, 2024)
„The overall aim of this paper is to increase the comprehensiveness of the German Labour Market Ontology (GLMO). The GLMO provides entities for qualifications, such as occupations and training programs, as well as tools and skills. However, like most knowledge graphs, the GLMO provides only partially complete relationships between entities. This, for instance, affects the mappings of related tools, skills, and qualifications. To enrich the GLMO, publicly available data from the platforms of the Federal Employment Agency are extracted and combined with the GLMO. This integration process has led to the creation of additional entity classes for occupational metadata, including activity fields or activity areas. Moreover, additional links between skills.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; 370; Arbeitsmarktforschung; Datenanalyse; Qualifikationsprofil; Tätigkeitsfelder